Análisis de actividades en textos de Física y Química de 2º de BUP - Bullejos de la Higuera, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
An analysis of the activities proposed by some textbooks has been made. The procedure followed was to determine the operative behaviour involved in such activities to be classified accordine to a taxonornical model of objectives for experimental science. The distribution of the activities in each textbook has been represented, by means of percentage values, in graphs in order to establish comparisons. An evaluation of the underlying pedagogical ideas, which can be inferred from the results of the analysis, has been made. As a result, two groups of textboks have been spotted, according to different pedagogical outlooks, and different points of view of the educational aims of science. The possiblecorrelation between the pedagogical outlook of most of the textbooks and the actual teaching to be mainly performed in the classroom has been indicated.